Philosophy of Science in the Scope of Education and Science Management - Widiya Sulistiawati (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2023)
Between science and philosophy which both use reflective thinking methods in an effort to understand the facts of life, these are critical philosophy and science, open-minded and highly committed to the truth. In this connection the philosophy of science will open up insight into what the substance of science actually is. . This is because the philosophy of science is a further study and reflection on science, thus it is an absolute requirement to oppose the disintegration of science. Apart from that, to maintain balance in the growth of existing sciences, through an understanding of the principles, background and relationships of a scientific activity. The philosophy of science clarifies the existence of science which requires other knowledge as a means of thinking and a means of scientific communication. These tools include language, logic, mathematics, statistics, and other data analysis techniques. Philosophy-based educational management is the management of educational resources based on a realistic study of nature and the meaning of life, which is carried out using rational, natural scientific, harmonious and critical thinking.